Kitab el-Kâmil fi’t-târîh - 880-01 İbnü'l-Esîr, İzzeddin, 1160-1233. (Leiden Leiden Leiden Leiden Leiden Leiden Leiden Leiden Leiden Leiden Leiden Leiden Leiden)
14 cilt (1. c. 535 sayfa ; 2. c. 448 sayfa ; 3. c. 436 sayfa ; 4. c. 470 sayfa ; 5. c. 468 sayfa ; 6. c. 379 sayfa ; 7. c. 87 sayfa indeks, 385 sayfa ; 8. c. 523 sayfa ; 9. c. 452 sayfa ; 10. c. 485 sayfa ; 11. c. 373 sayfa ; 12. c. 330 sayfa ; 13. c. lxxxiii, 400 sayfa ; 14. c. sayfa 401-831, [1])